Discursive Construction of Social Reality: Conceptual Foundations and Empirical Devices for Unmasking the “Abominable” Practices - Ирина Троцук (Russian Sociological Review, 2014)
Review: Van Dijk T. A. (2014) Diskurs i vlast': reprezentacija dominirovanija v jazyke i kommunikacii [Discourse and Power: Representation of Domination in Language and Communication] (in Russian), Moscow: Librokom, 344 p. ISBN 978-5-397-04375-5